2021
DOI: 10.2147/ijn.s284518
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-Targeted Photosensitizer Nanoparticles for Photothermal and Photodynamic Therapy of Breast Carcinoma

Abstract: Purpose The near-infrared fluorescent dye indocyanine green (ICG) has shown great potential in the photodynamic therapy (PDT) and photothermal therapy (PTT) of cancer. However, its disadvantages of instability in aqueous solution, short half-life, and non-targeting accumulation limit the effectiveness of ICG PDT/PTT. To overcome the disadvantages of ICG in tumor treatment, we designed PEGylated-human serum albumin (PHSA)-ICG-TAT. In this nanoparticle, PEG4000, the HSA package, and nuclear targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Gracias a su fácil segregación y procedimiento permite una multifincionalidad al modificar un polielectrolito mediante la agregación de polímeros, nanopartículas orgánicas o incluso nanotubos de carbono (Karabasz, Bzowska, & Szczepanowicz, 2020). Su avance durante los últimos años ha permitido la creación de sistemas de administración de fármacos multifuncionales por sus condiciones, en donde se puede desarrollar una incorporación de la proteína objetivo a un direccionamiento de anticuerpos presentes sobre la célula objetivo manteniendo un ambiente controlado, otra aplicación recae en el uso de nanopartículas magnéticas que interactúan sobre un campo magnético externo generado por un nanoportador productor de cargas eléctricas, este tipo de atracción ha permitido la investigación celular en la reparación de tejidos, administración de fármacos, imágenes de resonancia magnética (Liu, et al, 2021;Gomha, et al, 2021).…”
Section: Construcción De Andamiosunclassified
“…Gracias a su fácil segregación y procedimiento permite una multifincionalidad al modificar un polielectrolito mediante la agregación de polímeros, nanopartículas orgánicas o incluso nanotubos de carbono (Karabasz, Bzowska, & Szczepanowicz, 2020). Su avance durante los últimos años ha permitido la creación de sistemas de administración de fármacos multifuncionales por sus condiciones, en donde se puede desarrollar una incorporación de la proteína objetivo a un direccionamiento de anticuerpos presentes sobre la célula objetivo manteniendo un ambiente controlado, otra aplicación recae en el uso de nanopartículas magnéticas que interactúan sobre un campo magnético externo generado por un nanoportador productor de cargas eléctricas, este tipo de atracción ha permitido la investigación celular en la reparación de tejidos, administración de fármacos, imágenes de resonancia magnética (Liu, et al, 2021;Gomha, et al, 2021).…”
Section: Construcción De Andamiosunclassified
“…With low afford and high biosafety, ICG has often been used in fundus choroidal angiography 23 and commonly acted as a good photoacoustic imaging agent in many studies. 24 , 25 In addition to imageology functions, it is noteworthy that ICG also has excellent photothermal/photodynamic properties under the same excitation laser. 26 Given the limited photodynamic effects of ICG caused by hypoxia in the tumor microenvironment, PFH is considered an excellent option to remedy the deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Under laser irradiation, the ICG also produces photodynamic (PDT) effects, therefore PDT and PTT are oen combine used. [26][27][28][29] Nevertheless, researchers were more inclined to study ICG-based PTT since ICG produces stronger photothermal effect. Besides, the poor optical and thermal stability of ICG as PTN limited its further applications.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Studies have shown that the polymer encapsulated clinical ICG nanoparticles can not only increase the stability of nanoparticles, but also could enhance PDT/PTT effect, meanwhile strengthen biocompatibility of the NPs with negligible toxicity. [27][28][29] Poly(styrene-co-maleic anhydride) (PSMA) is an amphiphilic polymer 40 and oen selected as encapsulation matrix for organic dyes to increase their chemical stability and biocompatibility. [41][42][43][44][45] In addition, PSMA has been used clinically and its covalent binding to proteins has been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation